2022
DOI: 10.1242/dev.200049
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic profiling and functional interpretation of histone lysine crotonylation and lactylation during neural development

Abstract: Metabolites such as crotonyl-CoA and lactyl-CoA influence gene expression by covalently modifying histones, known as histone lysine crotonylation (Kcr) and lysine lactylation (Kla). However, their existence patterns, dynamic changes, biological functions,and associations with histone lysine acetylation and gene expression during mammalian development remain largely unknown. Here, we find that histone Kcr and Kla are widely distributed in the brain and undergo global changes during neural development. By profil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 61 publications
(94 reference statements)
0
27
0
Order By: Relevance
“…For instance, a recent discovery indicates that histone lactylation and crotonylation are crucial for epigenetic regulation of brain development. In this work, lactylation and crotonylation were shown to have a synergistic effect on the processes of neural differentiation and cell proliferation ( Dai et al, 2022 ). Lactylation may also be related to butyrylation mediated by butyric acid because butyric acid contributes to an increased lactylation level of whole protein in Hela cells and may prevent lactylation via inhibiting a wide range of HDACs.…”
Section: Histone Lactylationmentioning
confidence: 99%
“…For instance, a recent discovery indicates that histone lactylation and crotonylation are crucial for epigenetic regulation of brain development. In this work, lactylation and crotonylation were shown to have a synergistic effect on the processes of neural differentiation and cell proliferation ( Dai et al, 2022 ). Lactylation may also be related to butyrylation mediated by butyric acid because butyric acid contributes to an increased lactylation level of whole protein in Hela cells and may prevent lactylation via inhibiting a wide range of HDACs.…”
Section: Histone Lactylationmentioning
confidence: 99%
“…Histone Kla is also widely distributed in the brain, and the level of histone H1Kla in the brain increases in response to the expression of the neuronal activity marker c-Fos and the neural excitation induced by Repeated social defeat stress (SDS) (105). H3K18la is involved in remodeling transcriptome expression and activates transcription in brain neurons (97).…”
Section: Lactylation Of Hcc Histone Lactylationmentioning
confidence: 99%
“…Furthermore, it has been shown that lactylation on the glycolytic enzyme ALDOA serves to allosterically inhibit its enzymatic activity, potentially mediating a negative feedback loop for the glycolysis pathway in the presence of excess lactic acid [ 283 ]. Finally, the functional relevance of lactylation has also been reported in RNA splicing, neurodevelopment, osteoblast differentiation, and cancer progression [ 285 , 286 , 287 , 288 ]. While there are no published studies of lactylation in PCa at this time, it is likely that this novel PTM will be validated as functionally relevant in promoting PCa progression, especially with respect to having regulatory effects on metabolic pathways and immunosuppressive effects on various components of anticancer immunity.…”
Section: Metabolites and Gene Regulationmentioning
confidence: 99%